2024
DOI: 10.3390/ijms25042147
|View full text |Cite
|
Sign up to set email alerts
|

Normal Proteasome Function Is Needed to Prevent Kidney Graft Injury during Cold Storage Followed by Transplantation

Dinesh Bhattarai,
Seong-Ok Lee,
Lee Ann MacMillan-Crow
et al.

Abstract: Kidney transplantation is the preferred treatment for end-stage kidney disease (ESKD). However, there is a shortage of transplantable kidneys, and donor organs can be damaged by necessary cold storage (CS). Although CS improves the viability of kidneys from deceased donors, prolonged CS negatively affects transplantation outcomes. Previously, we reported that renal proteasome function decreased after rat kidneys underwent CS followed by transplantation (CS + Tx). Here, we investigated the mechanism underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Bhattarai et al had previously demonstrated that the peptidase activity of the constitutive proteasome was decreased in kidney cells after cold storage and that this led to reduced graft function, potentially by impairing mitochondrial function. 5 7 The immunoproteasome differs from the constitutive proteasome in that several of the constitutively expressed catalytic β subunits of the standard proteasome are replaced by immunoproteasome-specific inducible counterparts. 8 These include the immunoproteasome-specific subunits LMP2 for constitutive β 1, LMP10 for β 2, and LMP7 for β 5.…”
mentioning
confidence: 99%
“…Bhattarai et al had previously demonstrated that the peptidase activity of the constitutive proteasome was decreased in kidney cells after cold storage and that this led to reduced graft function, potentially by impairing mitochondrial function. 5 7 The immunoproteasome differs from the constitutive proteasome in that several of the constitutively expressed catalytic β subunits of the standard proteasome are replaced by immunoproteasome-specific inducible counterparts. 8 These include the immunoproteasome-specific subunits LMP2 for constitutive β 1, LMP10 for β 2, and LMP7 for β 5.…”
mentioning
confidence: 99%